Admission control in multiservice IP networks : architectural issues and trends - Lima, Solange (2007)
The trend toward the integration of current and emerging applications and services in the Internet has launched new challenges regarding service deployment and management. Within service management, admission control (AC) has been recognized as a convenient mechanism to keep services under controlled load and assure the required QoS levels, bringing consistency to the services offered. In this context, this article discusses the role of AC in multiservice IP networks and surveys current and representative AC approaches. We address and compare the architectural principles of these AC approaches and their main features, virtues and limitations that impact on the quality control of network services. We identify important design aspects that contribute to the successful deployment of flexible and scalable AC solutions in multiservice networks.